Comparison of Total Leukocytes in Conventional Smokers and E-Smokers in Students of the Faculty of Medicine, University of Muhammadiyah North Sumatra - Barus, Putri; Irma, Fani (Health & Medical Sciences, 2025)
Smoking remains a widespread habit in Indonesia, particularly in Medan, where the prevalence of daily smokers reaches 55.2%, exceeding the national average of 54% in 2016. Despite awareness of the health risks associated with tobacco, many individuals continue smoking and some have shifted to e-cigarettes as an alternative. However, e-cigarettes are also known to have harmful effects on the body, including potential changes in leukocyte count. This study aimed to compare the total leukocyte count between conventional cigarette users and e-cigarette users. It employed an analytical observational approach with a cross-sectional design involving 60 respondents selected through purposive sampling based on inclusion and exclusion criteria. The results showed that most respondents had smoked for 1–5 years. Conventional cigarette users typically smoked 1–5 cigarettes per day, while e-cigarette users consumed 1–2 ml of liquid daily. The Mann-Whitney test produced a significance value of 0.525 (>0.05), indicating no significant difference in the total leukocyte count between conventional and e-cigarette users among medical students at the University of Muhammadiyah North Sumatra.